2016
DOI: 10.1039/c5tc04276c
|View full text |Cite
|
Sign up to set email alerts
|

Highly stable copper wire/alumina/polyimide composite films for stretchable and transparent heaters

Abstract: Thermal, electrical and mechanical stabilities of a Cu wire-based transparent heater are improved by coating alumina and polymide films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 57 publications
2
64
0
Order By: Relevance
“…[98,99] For practical application, the manufacturing process of wearable sensors should be cost-effective, scalable, capable of large area, and easy production. Park et al [101] have dip coated a fabric yarn to CuZr alloy (metallic glass)/PDMS Co-sputtering [12] Silver nanowire (Ag NW)/PDMS Vacuum filtration transfer [18] Silicone prepolymer/Al Spin coating [19] Ag-NW/styrene-butadiene-styrene (SBS) Solution casting [44] Ag-NW/cotton Dip coating [49] Silica NP/PDMS/cellulose acetate/IL/silver/cotton Coating/thermal evaporation [50] Aligned boron nitride (BN)/polyvinyl alcohol (PVA) 3D printing [51] PEDOT/cloth Coating/vapor phase polymerization [52] Nylon-6 nanofiber/Ag/nanoporous polyethylene (nano-PE) Electrospinning/electroless plating [53] Graphene/polyisobutylene (PIB)/PDMS Chemical vapor deposition/spin coating [54] Copper nanowire (Cu-NW)/poly (methyl methacrylate) (PMMA) Spray coating/spin coating [55] Cu wire/alumina/polyimide/PDMS Atomic layer deposition (ALD)/spin coating [178] Actuator/muscle MWCNT/carbon nanofiber/PEDOT:PSS Electrospinning/drop casting [6] Graphene oxide/vapor grown carbon fiber (VGCF)/IL Solution casting [8] PEDOT:PSS Wet spinning/ chemical treatment [17] Bacterial cellulose (BC)/IL/graphene Solution casting [23] PEDOT:PSS/VGCF/IL Solution casting [33] IL/polyurethane/PEDOT:PSS Solution casting [34] BC/IL/ionic polymer Dip coating [59] PEDOT-polystyrene sulfonic acid (PEDOT:PSS)/IL/BC Solution casting [179] Poly(ionic liquid)(PIL)/polyacrylic acid/paper Dip coating [65] Drug delivery Mesoporous silica nanoparticle Transfer printing [21] PDMS Soft lithography [61] www.advmat.de www.advancedsciencenews.com form a highly stretchable strain sensor that can stretch up to 150% along its axis while Lipomi et al [102] spray coated CNT to form a stretchable strain sensor. [100][101][102]…”
Section: Materials Structures and Methods In Wearable Sensorsmentioning
confidence: 99%
“…[98,99] For practical application, the manufacturing process of wearable sensors should be cost-effective, scalable, capable of large area, and easy production. Park et al [101] have dip coated a fabric yarn to CuZr alloy (metallic glass)/PDMS Co-sputtering [12] Silver nanowire (Ag NW)/PDMS Vacuum filtration transfer [18] Silicone prepolymer/Al Spin coating [19] Ag-NW/styrene-butadiene-styrene (SBS) Solution casting [44] Ag-NW/cotton Dip coating [49] Silica NP/PDMS/cellulose acetate/IL/silver/cotton Coating/thermal evaporation [50] Aligned boron nitride (BN)/polyvinyl alcohol (PVA) 3D printing [51] PEDOT/cloth Coating/vapor phase polymerization [52] Nylon-6 nanofiber/Ag/nanoporous polyethylene (nano-PE) Electrospinning/electroless plating [53] Graphene/polyisobutylene (PIB)/PDMS Chemical vapor deposition/spin coating [54] Copper nanowire (Cu-NW)/poly (methyl methacrylate) (PMMA) Spray coating/spin coating [55] Cu wire/alumina/polyimide/PDMS Atomic layer deposition (ALD)/spin coating [178] Actuator/muscle MWCNT/carbon nanofiber/PEDOT:PSS Electrospinning/drop casting [6] Graphene oxide/vapor grown carbon fiber (VGCF)/IL Solution casting [8] PEDOT:PSS Wet spinning/ chemical treatment [17] Bacterial cellulose (BC)/IL/graphene Solution casting [23] PEDOT:PSS/VGCF/IL Solution casting [33] IL/polyurethane/PEDOT:PSS Solution casting [34] BC/IL/ionic polymer Dip coating [59] PEDOT-polystyrene sulfonic acid (PEDOT:PSS)/IL/BC Solution casting [179] Poly(ionic liquid)(PIL)/polyacrylic acid/paper Dip coating [65] Drug delivery Mesoporous silica nanoparticle Transfer printing [21] PDMS Soft lithography [61] www.advmat.de www.advancedsciencenews.com form a highly stretchable strain sensor that can stretch up to 150% along its axis while Lipomi et al [102] spray coated CNT to form a stretchable strain sensor. [100][101][102]…”
Section: Materials Structures and Methods In Wearable Sensorsmentioning
confidence: 99%
“…The slope of the best-fit straight line in Figure 3f represents the heating efficiency (that is, thermal resistance) of the heater. 9,39 The heater that had a lower R s value had a steeper slope, implying better heating efficiency. Therefore, the remarkably low R s value of the AgNF heater was advantageous in reducing its thermal resistance for the efficient transduction of electrical energy into heat with lower power consumption.…”
Section: Thermal Characteristics Of a Agnf Heatermentioning
confidence: 99%
“…The obtained STC exhibited excellent electrical conductivity as well as high chemical and electrochemical stabilities compared to that prepared with pristine AgNWs. Li et al reported an STC comprising of Al 2 O 3 /CuNWs/polyimide film using atomic layer deposition. The oxide layer was deposited to ensure the unprecedented stability against harsh environment.…”
Section: Structure‐dependent Properties Of Stcsmentioning
confidence: 99%